PERHITUNGAN KEBIJAKAN INSENTIF PAJAK PENGHASILAN DI MASA PANDEMI COVID-19 - Gede Ngurah Indra Arya Aditya (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
Indonesia has officially declared that the Covid-19 pandemic has been declared a non-natural national disaster. This is stated through the Presidential Decree of the Republic of Indonesia Number 12 of 2020. Of course, when facing a pandemic period, taxpayers get the right to benefits because they have overcome the Covid-19 problem through the tax donations given. the government to issue a fiscal stimulus policy in the relaxation of Article 21 Income Tax with certain criteria set out in the Regulation of the Minister of Finance of the Republic of Indonesia Number 44/PMK.03/2020 concerning Tax Incentives for Taxpayers Affected by the Corona Virus Disease 2019 (Covid-19) Pandemic. Although the government's policy in terms of providing tax incentives has consequences for a decrease in state revenues from the tax sector, this policy can help reduce the domino effect caused by the Covid-19 pandemic on the national economy. This research is to help the general public and in particular individual taxpayers to be able to independently calculate Article 21 income tax, especially to ascertain whether taxpayers can obtain Income Tax Incentives that can help ease the economic burden affected by the spread of Covid-19 in Indonesia.